2006
DOI: 10.1074/jbc.m505951200
|View full text |Cite
|
Sign up to set email alerts
|

Enacyloxin IIa Pinpoints a Binding Pocket of Elongation Factor Tu for Development of Novel Antibiotics

Abstract: Elongation factor (EF-) Tu⅐GTP is the carrier of aminoacyl-tRNA to the programmed ribosome. Enacyloxin IIa inhibits bacterial protein synthesis by hindering the release of EF-Tu⅐GDP from the ribosome. The crystal structure of the Escherichia coli EF-Tu⅐guanylyl iminodiphosphate (GDPNP)⅐enacyloxin IIa complex at 2.3 Å resolution presented here reveals the location of the antibiotic at the interface of domains 1 and 3. The binding site overlaps that of kirromycin, an antibiotic with a structure that is unrelated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 31 publications
(41 reference statements)
6
66
0
Order By: Relevance
“…Arg5 Arg Arg5 Arg5 Arg5 Arg5 Arg5 A Arg5 Arg5 Arg5 Arg5 A g5 A A A A A A 9 9 9 9 9 9 9 9 9 9 9 9 9 (27) bound to enacyloxin IIA (blue sticks) and a nonhydrolyzable GTP-analog guanosine 5′-(β,γ-imido)triphosphate (GDPNP) (red). (E) Superimposition of E. coli EF-Tu (PDB ID: 1DG1) (26) and P. putida EF-Tu from the PPHD putida :EF-Tu complex; the switch I loop is highlighted (P. putida EF-Tu, blue; E. coli EF-Tu, red).…”
Section: Significancementioning
confidence: 99%
“…Arg5 Arg Arg5 Arg5 Arg5 Arg5 Arg5 A Arg5 Arg5 Arg5 Arg5 A g5 A A A A A A 9 9 9 9 9 9 9 9 9 9 9 9 9 (27) bound to enacyloxin IIA (blue sticks) and a nonhydrolyzable GTP-analog guanosine 5′-(β,γ-imido)triphosphate (GDPNP) (red). (E) Superimposition of E. coli EF-Tu (PDB ID: 1DG1) (26) and P. putida EF-Tu from the PPHD putida :EF-Tu complex; the switch I loop is highlighted (P. putida EF-Tu, blue; E. coli EF-Tu, red).…”
Section: Significancementioning
confidence: 99%
“…8a) and might also contribute to the kirromycin-resistant character of EF-Tu3. The binding site of enacyloxin IIa partially overlaps with the kirromycin binding site (28). The strong salt bridge between Lys313 and the antibiotic is no longer possible due to the K313A substitution in EF-Tu3.…”
Section: Discussionmentioning
confidence: 96%
“…3) In spite of these unique properties, synthetic study other than by our group has not been reported yet. On the continuation of our chemical works on ENXs, [5][6][7]9,10) we attempted to improve the synthesis of the cyclohexane moiety 3.…”
Section: )mentioning
confidence: 99%